Konsep Learner-Centered Design Kurikulum Dalam Pembinaan Dewasa Awal di Gereja - Duma Fitri Pakpahan; Junihot Simanjuntak; Victor Deak (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2022)
This study aims to explain one of the curriculum designs commonly used in the field of education, namely the learner-centered design that can be adopted by the church in order to design early adult development in the church according to the stage of development of church members. This study uses a descriptive qualitative method to describe the stages of implementing the Learner Centered design in designing the curriculum in the church. Based on the results of the study, it was found that: 1) the learner-centered design is very relevant to be used for coaching adults in the church in short and medium-term programs because it is practical, arranged based on needs and makes it easier for the congregation to understand the teaching of God's will in daily life and meet their development needs. 2) the stages that the church needs to prepare when implementing this curriculum design consist of an initial stage to analyze the needs of the congregation, a design stage that pays attention to the material, a relevant learning time strategy for students, and an evaluation stage to determine the success of the designed curriculum.